Transitioning to Performance-Based State Funding: Concerns, Commitment, and Cautious Optimism - Lindsay K. Wayt; Barbara Y. LaCost (Educational Considerations, 2016)
The introduction of performance-based state funding of higher education can be traced to the late 1970s. Early forms, referred to as Performance Funding 1.0, provided higher education institutions with bonuses, in addition to regular state funding, when they met certain state-defined outcomes. More recent forms, referred to as Performance Funding 2.0, have eliminated bonuses, and regular state funding has been replaced, in part or completely, with funding tied to achievement of state-defined performance goals, which often include student outcomes, like graduation and retention rates.
Keywords: performance-based; higher education; institutions; funding policies; students implementation; Optimism; participants; administrators; faculty